2016
DOI: 10.1104/pp.16.00289
|View full text |Cite
|
Sign up to set email alerts
|

eQTL Regulating Transcript Levels Associated with Diverse Biological Processes in Tomato

Abstract: Variation in gene expression, in addition to sequence polymorphisms, is known to influence developmental, physiological, and metabolic traits in plants. Genetic mapping populations have facilitated identification of expression quantitative trait loci (eQTL), the genetic determinants of variation in gene expression patterns. We used an introgression population developed from the wild desertadapted Solanum pennellii and domesticated tomato (Solanum lycopersicum) to identify the genetic basis of transcript level … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 49 publications
6
46
0
Order By: Relevance
“…On the contrary, trans-acting eQTLs mostly presented low to moderate effects varying with watering conditions. Ranjan et al (2016) also identified in an interspecific progeny of tomato a majority of trans-acting eQTL.…”
Section: Genetic Control Of Expression Variation and Interaction Withmentioning
confidence: 91%
See 1 more Smart Citation
“…On the contrary, trans-acting eQTLs mostly presented low to moderate effects varying with watering conditions. Ranjan et al (2016) also identified in an interspecific progeny of tomato a majority of trans-acting eQTL.…”
Section: Genetic Control Of Expression Variation and Interaction Withmentioning
confidence: 91%
“…Several transcriptomic analyses have revealed the evolution of gene expression levels along tomato fruit development (Tomato Genome Consortium, 2012) or in different fruit tissues (Carrari et al, 2006;Mounet et al, 2009;Matas et al, 2011;Pattison et al, 2015;Zhang et al, 2016). The genetic bases of these variations have been addressed for the first time by Ranjan et al (2016), revealing 7225 loci that regulate the steady-state transcript levels of 5289 genes using an introgression line population derived from the wild relative species S. pennellii. More recently, Zhu et al (2018) performed transcriptome-based association mapping in a collection of 399 diverse tomato genotypes and identified 2566 cis eQTLs and 93 587 trans eQTLs involved in the expression level variations of 3465 genes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to understand the relationships between the candidate genes and their targets, we conducted DGE analysis with ANOVA and selected 9776 DEGs with FDR less than 0.1 (Table S6). Next, we used Barnes-Hut t-distributed stochastic neighbor embedding (BH-SNE) 20 to generate gene clusters based on gene expression patterns (Data S4) (23). Among the 85 gene clusters generated (Table S7), four clusters were selected based on their GO (Gene Ontology) enrichment terms ( Fig.…”
Section: Regulatory Mechanisms and Network Leading To Resistance Resmentioning
confidence: 99%
“…Together these two clusters contained the majority of the literature-curated leaf development genes used for the candidate gene search (Ichihashi et al 2014;Ranjan et al 2016). The IRanges R/Bioconductor package (Lawrence et al 2013) was used to find the overlaps between the IL trans-eQTL and the BIL epistatic QTL.…”
Section: Il Eqtl Enrichment Among Bil Epistatic Qtlmentioning
confidence: 99%